Site‐directed mutagenesis around the CuA site of a polyphenol oxidase from Coreopsis grandiflora (cgAUS1). Issue 7 (16th February 2015) - Kaintz, Cornelia; Mayer, Rupert L.; Jirsa, Franz; Halbwirth, Heidi; Rompel, Annette
Abstract : Aurone synthase from Coreopsis grandiflora ( cg AUS1), catalyzing conversion of butein to sulfuretin in a type‐3 copper center, is a rare example of a polyphenol oxidase involved in anabolism. Site‐directed mutagenesis around the CuA site of AUS1 was performed, and recombinant enzymes were analyzed by mass spectrometry. Replacement of the coordinating CuA histidines with alanine resulted in the presence of a single copper and loss of diphenolase activity. The thioether bridge‐building cysteine and a phenylalanine over the CuA site, exchanged to alanine, have no influence on copper content but appear to play an important role in substrate binding. Abstract : Site‐directed mutations of AUS1 around the CuA site were generated and verified. All mutations led to loss of diphenolase activity with butein as substrate. Exchange of histidines in the CuA resulted in enzymes containing only one Cu. F273 mutation to alanine did not increase the monophenolase activity. C97 mutation eliminated the diphenolase activity, but 2 Cu atoms were incorporated.